Review of Development Towards Minimum Quantity Lubrication and High Speed Machining of Aluminum 7075-T6 - Zainol, A.; Yazid, M.Z.A (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Nowadays, the challenge in machining industries is focused on achieving high-quality product on component accuracy, and high production rate. It is necessary to enhance existing technology and develop the product with reasonable cost. Thus, researchers have developed advanced technology such as high-speed machining. High-speed machining plays a very important role in achieving cost and time savings together with better surface finish and dimensional accuracy. High-speed machining is being widely employed in the aerospace industry. Aluminum 7075-T6 is one of the popular materials with attractive properties such as high tensile strength, toughness and high corrosion resistance. Minimum quantity lubrication is known as a technique to provide the best cutting performances. This paper provides the recent studies in minimum quantity lubrication and high-speed machining of aluminum 7075-T6. The influence of high-speed machining process parameters in term the surface roughness and relevant cutting fluid technique have been discussed based on the findings of the recent studies.